The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5815/ijmecs.2015.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Using Unified Theory of Acceptance and Use of Technology Model to Predict Students’ Behavioral Intention to Adopt and Use E-Counseling in Ghana

Abstract: Abstract-The urge to progressively motivate ecounselling in schools is somewhat dependent on students" behavioural intention towards the use of counselling technologies. This paper presents an empirical approach of using Unified Theory of Acceptance and Use of Technology model to ascertain students" behavioural intention to adopt and use e-counselling in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Good performance expectancy with indicators of perceived usefulness, extrinsic motivation, job suitability, relative advantage, and expectations of the results of filling in patient health data into the EMR would cause the health professions to have the intention and commitment to carry out work that will ultimately fill the EMR. The results of this study also indicated that performance expectations have a direct, partial effect on behavioral intentions, such as enthusiasm, persuasion, and willingness (Emmanuel et al, 2015); (Tarhini et al, 2016); (Ramdhani et al, 2017); (Sharifian et al, 2014); (Ma et al, 2016); (Archer & Cocosila, 2011); (Shiferaw & Mehari, 2019); (Bawack & Kala Kamdjoug, 2018); (Wrzosek et al, 2020); (Abdekhoda & Salih, 2017); (Fatimatus Zayniyah, 2016) ; (Gagnon et al, 2014); and this is not line with the result of the study (Enaizan et al, 2020).…”
Section: Resultscontrasting
confidence: 59%
“…Good performance expectancy with indicators of perceived usefulness, extrinsic motivation, job suitability, relative advantage, and expectations of the results of filling in patient health data into the EMR would cause the health professions to have the intention and commitment to carry out work that will ultimately fill the EMR. The results of this study also indicated that performance expectations have a direct, partial effect on behavioral intentions, such as enthusiasm, persuasion, and willingness (Emmanuel et al, 2015); (Tarhini et al, 2016); (Ramdhani et al, 2017); (Sharifian et al, 2014); (Ma et al, 2016); (Archer & Cocosila, 2011); (Shiferaw & Mehari, 2019); (Bawack & Kala Kamdjoug, 2018); (Wrzosek et al, 2020); (Abdekhoda & Salih, 2017); (Fatimatus Zayniyah, 2016) ; (Gagnon et al, 2014); and this is not line with the result of the study (Enaizan et al, 2020).…”
Section: Resultscontrasting
confidence: 59%
“…This study focused on assessing the nurses' feedback on WMMS, which includes (1) acceptance, (2) usability, and (3) experience. First, the perceived acceptance of WMMS was measured using the Unified Theory of Acceptance and Use of Technology model 12,13 with a Cronbach's α of .87 14 . It consists of four primary constructs, namely, (1) performance expectancy, the belief that using the system can improve job performance; (2) effort expectancy, the user-friendliness of the system; (3) social influence, the perception of other people about the system; and (d) facilitating conditions, the availability of resources to use the system feasibly.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to referring to TAM, this study also bases its concept on the Unified Theory of Acceptance and Use of Technology Model (UTAUT) developed by Venkatesh et al (2003). The idea of UTAUT refers to eight models that examine behavior, among others Theory of Reasoned Action (TRA), Motivational Model/MM, TAM Theory of Planned Behavior/TPB, a combined Theory of Planned Behavior and Technology Acceptance Model/TPB-TAM, Model of Personal Computer use and a combined Theory of Diffusion of Innovations Theory/MPC-TDIT, and Socio Cognitive Theory (SCT) (Kolog et al 2015).…”
Section: Unified Theory Of Acceptance and Use Of Technology Model (Utmentioning
confidence: 99%